Redefining Social Responsibility Through AI Literacy: The Roles of Digital Literacy and Ethical Awareness in Digital Citizenship - Misbahuljannah; Riqqah Dhian Shefira; Devi Miftahul Jannah; Muh. Yusril Anam; Rosidah (Journal of Applied Artificial Intelligence in Education, 2026)
The rapid integration of artificial intelligence (AI) into digital learning environments requires higher education students to develop not only technical competence, but also critical, ethical, and socially responsible capacities as digital citizens. This study aims to examine how AI literacy, digital literacy, and ethical awareness influence students’ social responsibility as a key foundation for responsible digital citizenship. A quantitative cross-sectional survey was conducted with 100 undergraduate students in Informatics and Computer Engineering Education, and the hypothesized relationships were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that digital literacy has a positive and significant effect on social responsibility (β = 0.397, p = 0.001) and ethical awareness emerges as the strongest positive predictor (β = 0.615, p < 0.001), while AI literacy exhibits a negative but significant effect (β = −0.151, p = 0.022), suggesting that higher AI literacy may foster more critical or cautious orientations that could reduce socially responsible engagement when not accompanied by strong ethical grounding and citizenship-oriented competencies. The findings imply that higher education curricula should integrate digital literacy, AI literacy, and ethics education in a balanced manner moving beyond purely technical training so that AI literacy translates into constructive social responsibility and strengthened digital citizenship; future studies should extend the sample and adopt longitudinal designs to capture behavioral changes over time.